Carbonation of minerals and slags under high pressure in an autoclave - Matus, Carlos F.; Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Carbonation of minerals (olivine and wollastonite) and secondary materials such as slag under high pressure in autoclaves has high importance due to environmetal problems.Methods: The most important for this process is to have a good knowledge of the behavior of carbon dioxide in water solution under high pressure, the precipitation of silica, dissolution of metals such as nickel and magnesium as well as subsequent filtration.Results:  The carbonation process of olivine und slag under high pressure (from 40 to 80 bar) in an autoclave was successfully performed at 175°C, with and without additivies.Conclusion: A comparative analysis has confirmed better carbonation of slag (max. 300 kg/ton) in comparison to that of olivine (max. 70 kg/ton) under the same conditions.
Keywords: carbonation; olivine; slag; autoclave; additives